Inhibition of trichloroethylene oxidation by the transformation intermediate carbon monoxide. - Henry, S M (1991)
Inhibition of trichloroethylene (TCE) oxidation by the transformation intermediate carbon monoxide (CO) was evaluated with the aquifer methanotroph Methylomonas sp. strain MM2. CO was a TCE transformation intermediate. During TCE oxidation, approximately 9 mol% of the TCE was transformed to CO. CO was oxidized by Methylomonas sp. strain MM2, and when formate was provided as an electron donor, the CO oxidation rate doubled. The rate of CO oxidation without formate was 4.6 liter mg (dry weight)-1 day-1, and the rate with formate was 10.2 liter mg (dry weight)-1 day-1. CO inhibited TCE oxidation, both by exerting a demand for reductant and through competitive inhibition. The Ki for CO inhibition of TCE oxidation, 4.2 microM, was much less than the Ki for methane inhibition of TCE oxidation, 116 microM. CO also inhibited methane oxidation, and the degree of inhibition increased with increasing CO concentration. When CO was present, formate amendment was necessary for methane oxidation to occur and both substrates were simultaneously oxidized. CO at a concentration greater than that used in the inhibition studies was not toxic to Methylomonas sp. strain MM2.